2017
DOI: 10.1111/lam.12789
|View full text |Cite
|
Sign up to set email alerts
|

Synergy and mechanism of action of α-mangostin and ceftazidime against ceftazidime-resistant Acinetobacter baumannii

Abstract: Significance and Impact of the Study: Acinetobacter baumannii strains cause serious infections, patient mortality, and have been reported to rise of multidrug resistance. This article represents the first report of using α-mangostin plus ceftazidime against these resistant strains and its mechanism of action. α-mangostin has no cytotoxic effects. Therefore, α-mangostin has strong potential for development as a useful, novel adjunct phytopharmaceutical to ceftazidime synergistically for the treatment of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The data were expressed as a mean ± standard error of the mean (SEM). Significant differences between these groups were examined using one-way ANOVA and Tukey's HSD post hoc test; p < 0.01 were considered to be a significant statistical difference [ 25 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The data were expressed as a mean ± standard error of the mean (SEM). Significant differences between these groups were examined using one-way ANOVA and Tukey's HSD post hoc test; p < 0.01 were considered to be a significant statistical difference [ 25 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…These findings are consistent with the fact that XDRAB has been increasingly isolated in clinical settings globally, which calls for combination therapy 11 . Indeed, the clinical choice of antibacterial drugs for XDRAB infections is limited, and the new therapeutic regime with combination drug use has been pursued 16,17,20,21 . Given that biofilms contribute to bacterial virulence and resistance 22 , we targeted agents with anti-biofilm property for their potential in combination drug use against A. baumannii.…”
Section: Discussionmentioning
confidence: 99%
“…Another extract, silymarin, can improve the toxicity of linezolid and synergistic anti-MRSA infection, while a high concentration silibinin with kanamycin can inhibit the growth of S. aureus. Pimchan et al (2017) demonstrated a synergistic effect between α-mangostin and ceftazidime in A. baumannii. The FICI of the combination of α-mangiferin and oxacillin against oxacillin-resistant Staphylococcus saprophyticus was 0.37.…”
Section: Review Flavonoids Combined With Antibiotics For Antibacteria...mentioning
confidence: 91%